2024
DOI: 10.3390/nu16040486
|View full text |Cite
|
Sign up to set email alerts
|

Non-Interventional Weight Changes Are Associated with Alterations in Lipid Profiles and in the Triglyceride-to-HDL Cholesterol Ratio

Shiri Weinstein,
Elad Maor,
Alon Kaplan
et al.

Abstract: Background: Obesity is associated with dyslipidemia, and weight loss can improve obese patients’ lipid profile. Here, we assessed whether non-interventional weight changes are associated with alterations in lipid profile, particularly the triglyceride (TG)-to-high-density lipoprotein cholesterol (HDL-C) ratio (TG/HDL-C). Methods: In this retrospective analysis of subjects referred to medical screening, body mass index (BMI), low-density lipoprotein cholesterol (LDL-C), TG, and HDL-C levels were measured annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
(78 reference statements)
1
1
0
Order By: Relevance
“…Interestingly, we have recently shown that the triglycerides-tohigh-density-lipoprotein-cholesterol ratio (TG/HDL-C) is closely associated with minor non-interventional weight changes. Therefore, these data, along with our current findings, further highlight the importance of minor weight changes, as well as triglycerides and serum uric acid, in cardiovascular risk stratification [33,34]. In a multivariable regression analysis, we found that male sex and hypertension, which are traditional cardiovascular risk factors, were also associated with an increase in serum uric acid, further emphasizing the association of serum uric acid with classic metabolic risk factors, as well minor non-interventional weight changes.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly, we have recently shown that the triglycerides-tohigh-density-lipoprotein-cholesterol ratio (TG/HDL-C) is closely associated with minor non-interventional weight changes. Therefore, these data, along with our current findings, further highlight the importance of minor weight changes, as well as triglycerides and serum uric acid, in cardiovascular risk stratification [33,34]. In a multivariable regression analysis, we found that male sex and hypertension, which are traditional cardiovascular risk factors, were also associated with an increase in serum uric acid, further emphasizing the association of serum uric acid with classic metabolic risk factors, as well minor non-interventional weight changes.…”
Section: Discussionsupporting
confidence: 78%
“…As previously described [33,34], every clinic visit included a completion of a standard questionnaire regarding participants' medical history, any recent medical events since their previous visit, and their demographic characteristics, as well as lifestyle and health-related habits. The weight and height of all subjects, wearing light clothes without shoes, were measured and recorded at each visit.…”
Section: Methodsmentioning
confidence: 99%